Corrosion analysis and remaining useful life prediction for storage tank bottom. (27th September 2019) - Feng, Yu; Yang, Yujiu; Huang, Biqing
Corrosion of large storage tank bottom has been identified as the main threat to tank security around the world. Corrosion detection becomes the main approach to ensure the safety of large storage tanks. In this article, we propose a two-stage tank bottom corrosion analysis and remaining useful life prediction framework. In the first stage, the causes and mechanisms of tank bottom corrosion are analyzed, the evaluation metric system is established, and the fuzzy comprehensive evaluation method is used to evaluate the health status of tank bottom. The preliminary evaluation result in the first stage determines whether a subsequent remaining useful life prediction is required. If the tank bottom is not in healthy state, in the second stage, the remaining useful life prediction of the tank bottom is implemented by acoustic emission and risk-based inspection. Both qualitative and quantitative evaluation are carried out to provide a basis for the operation and maintenance decision of storage tanks.